If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + 9 + -3t + -7 = 0 Reorder the terms: 9 + -7 + 9t + -3t = 0 Combine like terms: 9 + -7 = 2 2 + 9t + -3t = 0 Combine like terms: 9t + -3t = 6t 2 + 6t = 0 Solving 2 + 6t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6t = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 6t = 0 + -2 6t = 0 + -2 Combine like terms: 0 + -2 = -2 6t = -2 Divide each side by '6'. t = -0.3333333333 Simplifying t = -0.3333333333
| 0=y^2+10y+9 | | 3x-5=7x+x-15 | | 9-4w=-11 | | 5(1+4h)+2h=27 | | 12k+9m-2m-12k= | | 5a+2=3a+2 | | 3+2x=14-3x | | 35.00+0.75x=1.25x | | 3x+16=5-x | | 5h^2-15h-270= | | 2x+3+51=180 | | 2-6(z+1)=4(z-2)+10 | | 2s^2-128= | | 5(3b-5)=4(6b-2) | | 2x+3y=7800 | | 3+4x-3=13 | | 12a+3=25 | | 25+8x=7 | | -16=7[p+3]+30 | | 10t+15-10-6t= | | -12(10-11x)=-6(x-3) | | 210+10+400+x=1000 | | 4x-7+1=8 | | 3x-4x+1=5 | | -12(10-11x)=-6(-3) | | 2r^2-9r= | | 8u+20=4(2u+5) | | x+40=2x-20 | | 5x-4(-2)=5 | | ay+c=n | | B=y-mx | | 5n^2+9n-18=0 |